2018
DOI: 10.1097/md.0000000000012584
|View full text |Cite
|
Sign up to set email alerts
|

Eculizumab in a pregnant patient with laboratory onset of catastrophic antiphospholipid syndrome

Abstract: Rationale:Hypercoagulability and pregnancy morbidity are hallmarks of the antiphospholipid syndrome (APS). Catastrophic antiphospholipid syndrome (CAPS) is a potentially life-threatening omplication of APS, with widespread acute thrombotic microangiopathy (TMA) that can be precipitated by pregnancy and delivery and result in multiorgan damage. Unrestrained activation of the complement cascade is involved, favoring endothelial activation, tissue factor expression by leukocytes, and platelet aggregation. The com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…37 A recent study confirmed this finding and histologic examinations showed vasculopathy and intervillous thrombi as the most common finding in OAPS placentae. 38 Furthermore, treatment of catastrophic, multiorgan thrombi in APS with eculizumab, a complement blocking agent, 39,40 supports the role of complement activation in APS and will have implication on therapeutic perspectives especially in women who fail standard of care 41 and other therapies may emerge in the future. 33 The scientific discussion is still ongoing 42 and could result in additional therapeutic concepts.…”
Section: Definition-laboratory Criteria and Testingmentioning
confidence: 89%
“…37 A recent study confirmed this finding and histologic examinations showed vasculopathy and intervillous thrombi as the most common finding in OAPS placentae. 38 Furthermore, treatment of catastrophic, multiorgan thrombi in APS with eculizumab, a complement blocking agent, 39,40 supports the role of complement activation in APS and will have implication on therapeutic perspectives especially in women who fail standard of care 41 and other therapies may emerge in the future. 33 The scientific discussion is still ongoing 42 and could result in additional therapeutic concepts.…”
Section: Definition-laboratory Criteria and Testingmentioning
confidence: 89%
“…see [15]). Complement activation plays an important role in the pathogenesis, and molecular interventions targeting the pathway hold promise for prevention of the uncommon but life-threatening complication, the catastrophic APS (e.g.…”
Section: Hormones Complement and The Anti-phospholipid Syndromementioning
confidence: 96%
“…Complement activation plays an important role in the pathogenesis, and molecular interventions targeting the pathway hold promise for prevention of the uncommon but life-threatening complication, the catastrophic APS (e.g. see [15]). Proteins that physiologically curb the activation of complement, such as decay accelerating factor (DAF, CD55) and the membrane co-factor protein (MCP, CD46) are expressed in the placenta.…”
Section: Hormones Complement and The Anti-phospholipid Syndromementioning
confidence: 99%
“…47,49,50 It has also been suggested that low complement levels may be related to prematurity associated with the underlying disease. 51,52 Further data are needed to conclusively determine whether this drug is safe to be used during pregnancy. Although there are published cases of HS complicating pregnancy, ours is the first published case of hyperhemolysis prophylaxis in a pregnant patient.…”
Section: Hyperhemolysis Prophylaxismentioning
confidence: 99%